The secrets of love story bridge [large type] - Patrick, Phaedra (Center Point Large Print, 2020)
"It's summer in the city and passions are soaring along with the temperature - for everyone but Mitchell Fisher, who hates all things romance. He relishes his job cutting off the padlocks that couples fasten to the famous "love story" bridge. Only his young daughter, Poppy, knows that behind his prickly veneer, Mitchell still grieves the loss of her mother. Then one hot day, everything changes when Mitchell courageously rescues a woman who falls from the bridge into the river. He's surprised to feel an unexpected connection to her, but she disappears before he can ask her name. Desperate to find out her identity, Mitchell is shocked to learn she's been missing for almost a year. He teams up with her spirited sister, Liza, on a quest to find her again. However, she's left only one clue behind - a message on the padlock she hung on the bridge."--Publisher.